HIV disclosure in South Africa: Enabling the gateway to effective response - Norman, Amy; Chopra, Mickey; Kadiyala, Suneetha (International Food Policy Research Institute, 2005)
The sheer scale of the HIV/AIDS epidemic in sub-Saharan Africa has finally led to an expanded global response. South Africa, a nation where more than 5 million people are estimated to be HIV infected, has established large scale prevention and treatment programmes. Disclosure of one’s HIV status is an essential part of behaviour modification, access to HIV treatment and management programmes and for decreasing levels of community stigma. We examined the possible causes for widely differing rates of disclosure in two South African communities of similar ethnic and cultural mix. Qualitative interviews were carried out in 18 households with 25 individuals, and thematic analsyses was undertaken. Findings included the negotiation of HIV disclosure, the ‘unburdening’ of a positive status, and the ability to become involved in community activism and leadership. In both communities, disclosure was the catalyst for access to a variety of important, and often essential resources required to respond effectively to the impact of HIV/AIDS-related shocks. HIV positive people in the community with higher rates of disclosure had greater access formal institutional support through local NGOs and government social services and greater opportunities to take a positive leadership role as HIV positive individuals in the community. The creation of an enabling, resource-rich environment for HIV disclosure holds the potential to form a virtuous cycle whereby individuals are more likely to disclose, thus offering personal and community benefits, and further perpetuating disclosure at all levels within society.